Hurricane Keratopathy – “A Curlicue on The Cornea” - Vishnu Teja Gonugunta; Srinivasan Muthaiah (Delhi Journal of Ophthalmology)
Hurricane keratopathy is seen in the corneas with exaggerated epithelial cell turnover. It represents the path of proliferating epithelium visible by collection of pigment or iron within the corneal epithelium. It should be differentiated from cornea verticillata. Hurricane keratopathy is highlighted with fluorescein staining and not associated with drug deposition within the epithelium. Acute postoperative corneal steepening due to the surgical induced astigmatism causing decreased wetting of the cornea in addition to healing epithelial defect could be the cause of hurricane keratopathy appearance. Hurricane resolves once the stimulus for rapid epithelial turnover is eliminated.